Profile of Breast Diseases in Eastern Nepal - Bajracharya, Amir; Pangeni, Anang (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Breast problems, benign or malignant are common in occurrence worldwide. Breast problems can present themselves in a number of ways like breast pain, nipple discharge, cystic lesions and more commonly a lump. Breast diseases are under reported and cancer is one of the leading causes of mortality in women. This prospective study was undertaken with an aim to study the profile of various breast diseases in eastern Nepal. Materials & Methods: This is a prospective study of women with breast diseases conducted from March 2011 to February 2012. Inclusion criteria were women irrespective of age with breast diseases with or without complaints. Exclusion criteria were women having breast abscess and mammary fistula. Results: Out of 125 breast diseases 39 cases (31%) had malignancy and 86 cases (69%) had BBD. The overall mean age for BBD was 25.9 years, with range of 10-60 years. The mean age for malignant breast diseases was 45.6 years, with range of 28-67 years. All of the cases had breast lump as their presenting complaints whether they came out benign or malignant. 52.8% had no significant pain associated with lump; in malignant cases 35.8% had pain associated with lump. In benign cases 68.7% had no perceptible change in lump size. On ultrasound scan, 69% of the lesions were designated benign compared to 31% malignant features. FNAC resulted in 68% lesions to be classified as of benign nature and 32% as malignant /suspicious malignancy. Conclusion: BBD constituted 69% of breast diseases, and mostly fibroadenoma and FCC/FCD and commonest malignant lesion was infiltrating ductal carcinoma. The BBD peaked at the age of 21-30 years.